Change in charge carrier dynamics by incorporating ionic liquid into poly ethylene oxide–based sodium acetate polymer electrolytes. (August 2022) - Gupta, Sandhya; Singh, Pramod K; Bhattacharya, B
Poly (ethylene oxide) based sodium ion conducting solid polymer electrolytes films (salt NaCH3 COO) with varying amounts of an ionic liquid, 1-ethyl 3-methylimidazolium thiocyante were prepared by solution-cast method. All the prepared samples were characterized in detail for their ion transport characteristics at room temperature and temperature dependent behavior as well using electrochemical impedance spectroscopy. The measurement of ionic conductivity shows the many fold enhancement due the incorporation of ionic liquid in the polymer electrolyte matrix. The charge carrier density and mobility of charge carriers has been calculated and used for explaining the conductivity variations in these films. The increase in conductivity has been explained in terms of plasticization effect of ionic liquid and number of charge carriers per unit volume of electrolyte.